The Pandemic of Being a Woman: A Qualitative Analysis of the South African Media on GBV at the Time of COVID-19 - Carr, Kajal (Department of Psychology, 2023)
A decolonial feminist discourse analysis of the media's reporting on Gender Based Violence (GBV) during the first year of the COVID-19 pandemic was conducted. One hundred and fifty articles were collected from the Sabinet database. From this eight discourses were identified: GBV as a pandemic; GBV as genderless; women as vulnerable; the marginalization of victims; coddling men; redistributing fear; the co-option of GBV; and GBV as a systemic issue of power. It is argued that the media maintained the relevance and newsworthiness of GBV throughout the COVID 19 pandemic by borrowing legitimacy from COVID 19 in various ways. While this, along with the presence of more contextualized understandings of GBV, is a success, this paper argues that there is still work to be done on the way GBV is reported in the media. The data set demonstrated reductionist, uncontextualized and highly gendered representations of GBV that uphold colonial ideals of masculinity and femininity, while doing little to resist those power dynamics that uphold GBV. Recommendations for the media's reporting on GBV are made.